2020
DOI: 10.3390/ijerph17249193
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Characteristics in Grain Production and Its Influencing Factors in the Huang-Huai-Hai Plain from 1995 to 2018

Abstract: The Huang-Huai-Hai Plain is the major crop-producing region in China. Based on the climate and socio-economic data from 1995 to 2018, we analyzed the spatial–temporal characteristics in grain production and its influencing factors by using exploratory spatial data analysis, a gravity center model, a spatial panel data model, and a geographically weighted regression model. The results indicated the following: (1) The grain production of eastern and southern areas was higher, while that of western and northern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The GWR model can fully consider the spatial characteristics of each influencing factor, and it accurately depicts the spatial relationship between independent and dependent variables [58][59][60]. The formula is as follows [61]:…”
Section: Geographical Weighted Regression Model (Gwr)mentioning
confidence: 99%
“…The GWR model can fully consider the spatial characteristics of each influencing factor, and it accurately depicts the spatial relationship between independent and dependent variables [58][59][60]. The formula is as follows [61]:…”
Section: Geographical Weighted Regression Model (Gwr)mentioning
confidence: 99%
“…Meanwhile, research covers different scales of the whole country, river basins, provinces, and counties [12][13][14][15]. For example, some Chinese scholars conducted in-depth discussions on the Central Plains Economic Zone, the Huang-Huai-Hai Plain, and the Yangtze River Economic Belt, and found that most of the regional grain production spatial patterns tend to shift and change, with significant spatial correlation, agglomeration, and spillover effects, and the spatial agglomeration continues to increase [16][17][18]. These abundant studies are mostly based on "attribute characteristics".…”
Section: Introductionmentioning
confidence: 99%
“…Statistics also indicate that agricultural water use accounts for about 80% of the global total water consumption [ 2 ]. China is an important country for food production and consumption in the world [ 3 ]. However, the supply of cropland and water resources is insufficient in China, with per capita occupancy equal to 28% and 40% of the world average, respectively [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%